Measuring the Comfort of Tourist Visitors at Sukaerlaran Beach, Kakuluk Mesak District, Belu Regency - Hikmah, Hikmah; Edyan, Roly; Son, Aplonius (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of environmental sanitation and tourism management on tourist comfort at Sukaerlaran Beach, Belu Regency. This study was conducted using survey, ex-post facto, and associative methods. The population in this study consisted of visitors to Sukaerlaran Beach, Kakuluk Mesak District, Belu Regency. The sampling technique used in this study was non-probability sampling, specifically accidental sampling with the requirement that it was considered appropriate as a data source, namely a minimum of 100 respondents. Data were obtained through questionnaires. The analysis technique used was descriptive and inferential analysis. The results of the study showed that simultaneous and partial there was a positive and significant influence between environmental sanitation and tourism management on tourist comfort. This indicates that the better the condition of environmental sanitation and destination management, the higher the level of visitor comfort.